The prevalence of farmer burnout: Systematic review and narrative synthesis. (December 2022) - O'Shaughnessy, Branagh R.; O'Hagan, Anna Donnla; Burke, Aoife; McNamara, John; O'Connor, Siobhán
Abstract: Due to the economic, social, and health consequences of burnout, farmer burnout is receiving increased attention in the media and in contemporary research. In this systematic review and narrative synthesis, we aim to evaluate and synthesise the current state of the international evidence for the prevalence of farmer burnout. We developed and applied a search strategy to target studies that examined the prevalence of burnout among farmers of any farming type, gender, and nationality. Combined with secondary and grey literature searching, this resulted in 811 search results. Twenty-three full texts were screened which resulted in nine eligible studies consisting of seven cross-sectional studies, one longitudinal study, and one RCT. We applied the STROBE checklist for quality appraisal, and most studies had a low risk of bias. Across North American, European and Australian studies using cutting points, the average prevalence of severe burnout in farmers was 13.72%. The prevalence rate was higher in New Zealand (25%) and Morocco (18.96%). Compared to non-farmers, farmers experienced higher overall burnout, and higher exhaustion, cynicism and professional efficacy. Gender differences indicated that women experience higher burnout than males. Associated factors included farming as primary occupation, being a dairy farmer, and work stress. Findings indicate the characteristics of farmers especially at risk of burnout which could inform the development of future research and supports to ameliorate farmer burnout. Results also highlight the limitations of the evidence for farmer burnout including the lack of standardised burnout classification methods, the potential for response-bias when examining gender issues, and the influence of socio-economic and agricultural policy in the international evidence. Highlights: In this systematic review, we present current international literature on the prevalence of farmer burnout. Severe burnout in farmers ranged from 9.8%-13.72% depending on the measure used, cut-off points, and location Severe burnout was significantly higher in farmers compared to non-farmer populations. Burnout was higher in female farmers and in farmers outside Europe and North America. Factors associated with burnout were dairy farming, work stress, workload, health and traditional (non-diversified) farming